Long lasting effects of perinatal exposure to the Chlorpyrifos pesticide on sleep, breathing, and neuroinflammation in adult mice - Elena Miglioranza; Laura Rullo; Sara Alvente; Stefano Bastianini; Dario Coraci; Viviana Lo Martire; Loredana Maria Losapio; Gabriele Matteoli; Camilla Morosini; Emilia Volino; Alessandro Silvani; Roberto Rimondini; et al. (PLoS ONE, 2025)
Early-life exposure to environmental stressors may increase the risk of disease later in life. Chlorpyrifos (CPF), a widely used pesticide and acetylcholinesterase inhibitor, can cross the placental barrier and can be found in breast milk, leading to excessive cholinergic stimulation. Acetylcholine is involved in sleep and respiratory regulation. The main objective of this study was to investigate whether perinatal CPF exposure affects sleep-related breathing together with promotion of neuroinflammatory processes in adulthood. To explore these effects, CPF (5 mg/kg/day) or vehicle was administered orally to dams from mating to weaning. The offspring were not directly treated. At 17–18 weeks of age, male and female offspring underwent electroencephalographic and electromyographic electrode implantation to monitor sleep-wake cycles. Recordings were conducted over 48 hours in home cages, and for 7 hours in a plethysmographic chamber to assess sleep-related breathing pattern. At the end of recordings, hippocampal tissues were collected for gene expression analysis via real-time PCR. Results revealed that CPF perinatal exposure increased sighs and apneas during sleep in adult mice, especially in female. Additionally, expression of pro-inflammatory cytokines was upregulated while expression of peroxisome proliferator-activated receptor genes was downregulated in the hippocampus of female mice born to CPF-treated dams. These findings suggest that perinatal CPF exposure can induce long-lasting alterations in sleep-related respiratory patterns and hippocampal inflammatory responses, with a sex-specific susceptibility—females being more affected. This highlights the perinatal period as a critical window of vulnerability to environmental toxicants such as pesticides. The results support the hypothesis that adult sleep and brain inflammation phenotypes may be modulated by early-life chemical exposures during pregnancy and lactation.